The Urgency of Classification of the Voter List as a Fulfillment of Political Rights - Yandra, Alexsander; Faridhi, Adrian; Andrizal, Andrizal; Setiawan, Husni; Nurchotimah, Aulia Sholichah Iman (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
This study discusses the accuracy of the final voter list (DPT) with a focus on the process of classifying voter data. At the stage of determining the DPT by the Riau KPUD, it was found that 51,469 voters Did Not Meet the Requirements (Tidak Memenuhi Syarat/TMS) registered as permanent voters. On the other hand, there are still many potential voters who are 17 years old or married and are not registered as voters. This phenomenon is a problem that has always been an evaluation material for every general election organizer. This research was conducted using a qualitative method with a case study approach. Data were obtained by means of in-depth interviews with informants and collecting literature related to research issues. As a reference for analysis, this study uses the theory of democracy and the political rights of voters. The data were processed using an etic-emic approach so that a comprehensive analysis was found. The main argument of this research is that the classification and updating of data is an important step in determining the DPT to ensure that every citizen has good political rights.